2018
DOI: 10.3895/rbect.v11n1.5631
|View full text |Cite
|
Sign up to set email alerts
|

Determinação do nível de alfabetização científica de estudantes da etapa final do ensino médio e etapa inicial do ensino superior

Abstract: O artigo apresenta um panorama geral sobre Ensino de Ciência na abordagem de Alfabetização Científica e uma análise minuciosa sobre os dados da avaliação do nível de Alfabetização Científica de trinta alunos. Para fins analíticos, os participantes da pesquisa foram divididos em dois grupos, sendo o primeiro com quinze alunos do terceiro ano do ensino médio; e o segundo grupo com quinze alunos do curso de ensino superior séries iniciais na disciplina de Química Geral. O instrumento utilizado para realizar essa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…However, the analysis of the studies revealed that, in the case of 4 of the 5 main scientific literacy assessment instruments, some authors chose to change the analysis strategy of the original instrument, creating categories and/or modifying the categorization process and presentation of the results of the respondents' scientific literacy assessment. Gresczysczyn et al (2018), applying the TACB, assessed the average scientific literacy of groups rather than individuals, classifying as scientifically literate the groups whose average on the three subtests was higher than the minimum required hits. Oliveira and Silva-Forsberg (2012), using an adapted version of the TACB, categorized students' level of scientific literacy into "very good" (above 80% achievement), "good" (80% achievement), "satisfactory" (70% achievement), "regular" (60% achievement), and "below" (scores up to 50% achievement), with those who achieved at least the "regular" level being classified as scientifically literate.…”
Section: Ways Of Presenting and Analyzing The Results Of Scientific L...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the analysis of the studies revealed that, in the case of 4 of the 5 main scientific literacy assessment instruments, some authors chose to change the analysis strategy of the original instrument, creating categories and/or modifying the categorization process and presentation of the results of the respondents' scientific literacy assessment. Gresczysczyn et al (2018), applying the TACB, assessed the average scientific literacy of groups rather than individuals, classifying as scientifically literate the groups whose average on the three subtests was higher than the minimum required hits. Oliveira and Silva-Forsberg (2012), using an adapted version of the TACB, categorized students' level of scientific literacy into "very good" (above 80% achievement), "good" (80% achievement), "satisfactory" (70% achievement), "regular" (60% achievement), and "below" (scores up to 50% achievement), with those who achieved at least the "regular" level being classified as scientifically literate.…”
Section: Ways Of Presenting and Analyzing The Results Of Scientific L...mentioning
confidence: 99%
“…Among the 18 studies that adopted the TBSL and its versions-TACB, TACB-S, TACB-R, and adapted -, Camargo et al (2011), Gresczysczyn et al (2018), Laugksch and Spargo (1996a), Lima and Garcia (2015), Oliveira and Silva-Forsberg (2012), Rivas et al (2017), Vizzotto andDel Pino (2020a, 2020b), and Vizzotto and Mackedanz (2018) revealed that most of the students assessed are scientifically literate. The studies of Sousa (2019a, 2019b), Laugksch and Spargo (1999), Lima and Garcia (2013), Nascimento-Schulze (2006), Vizzotto (2019), and Vizzotto et al (2020, on the other hand, revealed that the majority of the students assessed did not reach the minimum number of hits required to be considered scientifically literate.…”
Section: Study Results: Performance In Scientific Literacy Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Todavia, a análise dos estudos revelou que, no caso de 4 dos 5 principais instrumentos de avaliação da literacia científica, alguns autores optaram por alterar a estratégia de análise do instrumento original, criando categorias e/ou modificando o processo de categorização e de apresentação dos resultados da avaliação da literacia científica dos inquiridos. Gresczysczyn et al (2018), aplicando o TACB, avaliaram a literacia científica média dos grupos e não dos indivíduos, classificando como cientificamente literatos os grupos cuja média no três subtestes foi superior ao mínimo de acertos necessários. Oliveira e Silva-Forsberg ( 2012), utilizando uma versão adaptada do TACB, categorizaram o nível de literacia científica dos alunos em "muito bom" (acima de 80% de aproveitamento), "bom" (80% de aproveitamento), "satisfatório" (70% de aproveitamento), "regular" (60% de aproveitamento) e "abaixo" (resultados até 50% de aproveitamento), sendo classificados como cientificamente literatos aqueles que atingiram, no mínimo, o nível "regular".…”
Section: Formas De Apresentação E Análise Dos Resultados Sobre a Lite...unclassified
“…Dentre os 18 estudos que adotaram o TBSL e as suas versões -TACB, TACB-S, TACB-R e adaptadas -, Camargo et al ( 2011), Gresczysczyn et al (2018), Laugksch e Spargo (1996a), Lima e Garcia (2015), Oliveira e Silva-Forsberg (2012), Rivas et al (2017), Vizzotto e Del Pino (2020a, 2020b e Vizzotto e Mackedanz (2018) revelaram que a maioria dos alunos avaliados é cientificamente literata. Já os estudos de Coppi e Sousa (2019a, 2019b, Laugksch e Spargo (1999), Lima e Garcia ( 2013 Nas sete pesquisas restantes, as quais aplicaram diferentes instrumentos de avaliação da literacia científica, os estudos de Atta e Aras (2020), Brossard e Shanahan (2006) e Rundgren et al (2010) revelaram médias de acertos nos itens acima dos 50%, ao passo que os estudos de Jannah et al (2020e Jufri et al (2019 indicaram médias abaixo dos 50% e o de Koedsri e Ngudgratoke (2018) relatou que os alunos não dominam os três atributos de literacia científica avaliados.…”
Section: Resultados Dos Estudos: Desempenho Na Avaliação Da Literacia...unclassified